The Influence Of Booklet Media On Mothers Of Toddlers Regarding Immunization - Afrida, Dewi; Simarmata, Mesrida (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Introduction : Infant mortality rate is still high, one of which is caused by infectious diseases. These infectious diseases can be prevented by immunization. Immunization can prevent babies from Tuberculosis (TB), Diphtheria, Tetanus, Hepatitis B, Pertussis, Measles, and Polio . Purpose : Effect Media Booklet on Knowledge and Attitude of Mothers of Toddlers about Complete Immunization . Population and Sample: mothers who have toddlers aged 18-24 years at Rini Clinic as many as 40 people with total population sampling technique, the number of samples is 40 people. Place and time: at the Rini Midwife Clinic, Sunggal District, Medan City, North Sumatra Province on month May – June 2024. Results : The majority of respondents aged 20-35 years were 24 people (60 % ), the majority of high school/equivalent education was 36 people ( 65 people), the majority of housewives were 23 people (58%), the majority of multigravida were 25 people (63%) . The mean score of knowledge before education was 53.38 and after education was 77.00. The attitude score before booklet media education was 15-25 and after the min-max was 22-29. From the Paired T Test The P value was found to be 0.000 < 0.05, so Ha was accepted, namely that there was a relationship between knowledge and attitudes before and after booklet media education for pregnant women and mothers of toddlers. About Basic Immunization Before administration at the Rini Midwife Clinic, Sunggal District, Medan City, North Sumatra Province in 2024. Conclusion : There is a relationship between knowledge and attitudes of mothers of toddlers before and after booklet media education About Basic Immunization at Rini Midwife Clinic, Sunggal District, Medan City, North Sumatra Province in 2024